Decline in the species richness contribution of Echinodermata to the macrobenthos in the shelf seas of China. (2015) - Jin, Shaofei; Wang, Yongli; Xia, Jiangjiang; Xiao, Ning; Zhang, Junlong; Xiong, Zhe
Highlights: Relative species richness (RSR) was used as a new metric for biodiversity change. A significant decline in the RSR of echinoderms was found in Chinese seas. There was no difference in the RSR between the period after and prior to 1997. Relative change in the RSR of echinoderms led to more relative change in biomass. Abstract: Echinoderms play crucial roles in the structure of marine macrobenthic communities. They are sensitive to excess absorption of CO2 by the ocean, which induces ocean acidification and ocean warming. In the shelf seas of China, the mean sea surface temperature has a faster warming rate compared with the mean rate of the global ocean, and the apparent decrease in pH is due not only to the increased CO2 absorption in seawater, but also eutrophication. However, little is known about the associated changes in the diversity of echinoderms and their roles in macrobenthic communities in the seas of China. In this study, we conducted a meta-analysis of 77 case studies in 51 papers to examine the changes in the contribution of echinoderm species richness to the macrobenthos in the shelf seas of China since the 1980s. The relative species richness (RSR) was considered as the metric to evaluate these changes. Trends analysis revealed significant declines in RSR in the shelf seas of China, the Yellow Sea, and the East China Sea from 1997 to 2009. Compared with the RSR before 1997, no significant changes in mean RSR were found after 1997, except in the Bohai Sea. In addition, relative change in the RSR of echinoderms and species richness of macrobenthos led to more changes (decrease or increase) in their respective biomasses. Our results imply that changes in species richness may alter the macrobenthic productivity of the marine benthic ecosystem.